2015
DOI: 10.1002/ejoc.201500207
|View full text |Cite
|
Sign up to set email alerts
|

Morita–Baylis–Hillman Reactions with Nitroalkenes: A Case Study

Abstract: We report on the use of a highly reactive super‐DMAP catalyst in Morita–Baylis–Hillman (MBH) reactions of nitroalkenes with ethyl glyoxylate, which result in excellent conversions and short reaction times with, importantly, very low catalyst loading. An extensive study of this particular reaction is presented, which examines all mechanistic and experimental details. Several critical points were hence uncovered that include the correlation between reaction efficiency and Lewis basicity of the catalyst; the doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…[27,49] This polymerization was evident from mass spectrometry (electrospray ionisation) throughout a one-pot reaction of 1a with DBU revealing molecular ion peaks with m/z ratios higher than 800 (see Table 3 in SI). [27,49] This polymerization was evident from mass spectrometry (electrospray ionisation) throughout a one-pot reaction of 1a with DBU revealing molecular ion peaks with m/z ratios higher than 800 (see Table 3 in SI).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[27,49] This polymerization was evident from mass spectrometry (electrospray ionisation) throughout a one-pot reaction of 1a with DBU revealing molecular ion peaks with m/z ratios higher than 800 (see Table 3 in SI). [27,49] This polymerization was evident from mass spectrometry (electrospray ionisation) throughout a one-pot reaction of 1a with DBU revealing molecular ion peaks with m/z ratios higher than 800 (see Table 3 in SI).…”
Section: Resultsmentioning
confidence: 96%
“…[41,42] While the buildup of N 2 was detected (see above) as comproportionation product of HNO and H 2 NOH, a degradation of HNO to N 2 O [45,46] (see Scheme 3e in SI) was not observed in the NMR kinetic measurements of 1a 15 N ( 15 N 2 O signals should appear at around 155 ppm and 240 ppm). [49] Next, the effects of different acids, substituents and bases were investigated to get further insights into the mechanism of the conjugated enyne formation. A carboxylic acid as additive accelerated significantly the formation of enyne and suppressed the formation of nitronate almost completely (compare a and b).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they performed the comparative study of electrophilicity of electrophiles and nitroalkenes responsible for the undesired polymerization during these reactions (Scheme 4). 23 For instance, they found that super-DMAP (17) (s-DMAP) was the best catalyst for this reaction.…”
Section: Scheme 3 Mbh and Rc Reactions Of Nitroalkenesmentioning
confidence: 99%
“…Nitro olefins including cyclic nitro olefins are resourceful intermediates in synthetic organic chemistry as well as in the chemical industry. They are also applied in various constructions of carbon–carbon bonds, such as the Michael reaction, Diels–Alder cycloaddition and Morita–Baylis–Hillman reaction . Besides, it is easy to transform the nitro group into other useful functional groups, for example, nitro compounds provide access to valuable synthetic precursors namely nitroalkanes, N‐substituted hydroxylamines, amines, ketones, oximes, α‐substituted oximes and α‐substituted ketones .…”
Section: Introductionmentioning
confidence: 99%
“…They are also applied in various constructions of carbon-carbon bonds, such as the Michael reaction, Diels-Alder cycloaddition and Morita-Baylis-Hillman reaction. [14][15][16] Besides, it is easy to transform the nitro group into other useful functional groups, for example, nitro compounds provide access to valuable synthetic precursors namely nitroalkanes, N-substituted hydroxylamines, amines, ketones, oximes, α-substituted oximes and α-substituted ketones. [17][18][19][20] Nitro olefins have extensive application in materials, pharmaceuticals, agrochemicals and so on.…”
Section: Introductionmentioning
confidence: 99%